2016
DOI: 10.4162/nrp.2016.10.5.530
|View full text |Cite
|
Sign up to set email alerts
|

Food deserts in Korea? A GIS analysis of food consumption patterns at sub-district level in Seoul using the KNHANES 2008-2012 data

Abstract: BACKGROUND/OBJECTIVESThe concept of "food deserts" has been widely used in Western countries as a framework to identify areas with constrained access to fresh and nutritious foods, providing guidelines for targeted nutrition and public health programs. Unlike the vast amount of literature on food deserts in a Western context, only a few studies have addressed the concept in an East Asian context, and none of them have investigated spatial patterns of unhealthy food consumption from a South Korean perspective.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…We found that physical proximity was not deemed a major barrier to accessing foods, yet the affordability of foods was considered a barrier. This finding is similar to the Korean context where financial and socio-behavioural rather than geographical barriers were seen to be more critical in terms of influencing food choice ( 32 ) . In our study, even if participants did not have access to highly processed and fried foods in their surrounding food environment they were preparing these foods themselves or accessing them from nearby towns.…”
Section: Discussionsupporting
confidence: 81%
“…We found that physical proximity was not deemed a major barrier to accessing foods, yet the affordability of foods was considered a barrier. This finding is similar to the Korean context where financial and socio-behavioural rather than geographical barriers were seen to be more critical in terms of influencing food choice ( 32 ) . In our study, even if participants did not have access to highly processed and fried foods in their surrounding food environment they were preparing these foods themselves or accessing them from nearby towns.…”
Section: Discussionsupporting
confidence: 81%
“…When purchasing FVs, consumers with higher education levels preferred freshness and safety over taste [28]. Interestingly, even though the proportion of individuals in Seoul, Korea with an insufficient food supply stemming from financial hardship had significantly decreased over time, one study found that a growing number of its people were consuming FVs less than once per day [43]. Therefore, dissecting the various underlying factors that shape the ever-changing interactions between demographics and FV consumption calls for extended longitudinal study.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…To date, most food environment studies have been conducted within the US, Australia, and New Zealand [15,29], though a growing number of studies have also be carried out in East Asian cities (e.g. [33][34][35][36][37][38]). There are significant differences between Western and Asian cities in terms of food environment patterns [33,39], population density and public transport provision [33], as well as social and cultural norms around food.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38]). There are significant differences between Western and Asian cities in terms of food environment patterns [33,39], population density and public transport provision [33], as well as social and cultural norms around food. More research focused on Asian cities and how people there interact with their food environments is needed to facilitate contextspecific policy formulation within the region.…”
Section: Introductionmentioning
confidence: 99%